Предмет:
МатематикаАвтор:
yakaddqn8 1/6 : (-1/2 - 2/3) + 5 · 1 2/9 = - 8/9
1) - 1/2 - 2/3 = - (3/6 + 4/6) = - 7/6
2) 8 1/6 : (-7/6) = 49/6 · (-6/7) = - 49/7 = - 7
3) 5 · 1 2/9 = 5 · 11/9 = 55/9 = 6 1/9
4) - 7 + 6 1/9 = - (7 - 6 1/9) = - (6 9/9 - 6 1/9) = - 8/9
Автор:
charismaДобавить свой ответ
Предмет:
ЛитератураАвтор:
tyreef1xoОтветов:
Смотреть
Предмет:
ОбществознаниеАвтор:
semajОтветов:
Смотреть
Предмет:
ФизикаАвтор:
ciprianoghivОтветов:
Смотреть
Предмет:
Русский языкАвтор:
acejhgdОтветов:
Смотреть